2009
DOI: 10.1093/aob/mcn259
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis reveals a scattered distribution of autumn colours

Abstract: The phylogenetic reconstruction suggests that autumn colours have been acquired and lost many times during evolution. This scattered distribution could be explained by hypotheses involving some kind of coevolutionary interaction or by hypotheses that rely on the need for photoprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 23 publications
6
66
0
1
Order By: Relevance
“…Lev-Yadun and Holopainen (2009) proposed that, as temperate deciduous trees go back to ancestors (Cretaceous or Tertiary) of tropical or sub-tropical origin (Axelrod, 1966;Milne and Abbott, 2002;Stebbins, 1974;Tiffney, 1985), it is possible to reconstruct a probable evolutionary route from young (e.g., Lee and Collins, 2001;Lee, 2007;Richards, 1996) and senescing (Lee and Collins, 2001) red leaves in tropical trees, through autumn-and winter-red leaves of evergreens (e.g., Chalker-Scott, 2002;Hughes and Smith, 2007), to red autumn leaves (e.g., Hoch et al, 2001;Lee et al, 2003;Matile, 2000) in trees that acquired the deciduous habit. The fact that out of 399 contemporary tropical tree species studied, some 13.5% expressed anthocyanin during senescence (Lee and Collins, 2001), a ratio similar to the 12.2% of species with red autumn leaves found by Archetti (2009a) in his broad taxonomic review of 2368 woody species of the current temperate floras, also supports the probable ancient origin of red autumn leaves. In this respect, since central Japan has more ancient Tertiary elements than Finland or Israel, it is expected that various patterns of leaf colouration that can be found in central Japan will not be found in the smaller woody floras of Finland and Israel.…”
Section: Tablesupporting
confidence: 57%
See 1 more Smart Citation
“…Lev-Yadun and Holopainen (2009) proposed that, as temperate deciduous trees go back to ancestors (Cretaceous or Tertiary) of tropical or sub-tropical origin (Axelrod, 1966;Milne and Abbott, 2002;Stebbins, 1974;Tiffney, 1985), it is possible to reconstruct a probable evolutionary route from young (e.g., Lee and Collins, 2001;Lee, 2007;Richards, 1996) and senescing (Lee and Collins, 2001) red leaves in tropical trees, through autumn-and winter-red leaves of evergreens (e.g., Chalker-Scott, 2002;Hughes and Smith, 2007), to red autumn leaves (e.g., Hoch et al, 2001;Lee et al, 2003;Matile, 2000) in trees that acquired the deciduous habit. The fact that out of 399 contemporary tropical tree species studied, some 13.5% expressed anthocyanin during senescence (Lee and Collins, 2001), a ratio similar to the 12.2% of species with red autumn leaves found by Archetti (2009a) in his broad taxonomic review of 2368 woody species of the current temperate floras, also supports the probable ancient origin of red autumn leaves. In this respect, since central Japan has more ancient Tertiary elements than Finland or Israel, it is expected that various patterns of leaf colouration that can be found in central Japan will not be found in the smaller woody floras of Finland and Israel.…”
Section: Tablesupporting
confidence: 57%
“…Under boreal conditions, even some genotypes of deciduous trees show this reddening following exposure to low temperatures (Taulavuori et al, 2011). The third case is season-related red autumn leaves (e.g., Archetti, 2009a;Hoch et al, 2001;Matile, 2000), with yellow autumn leaves particularly dominant in northern Europe (Holopainen and Peltonen, 2002) and red ones in other parts of the world (Lev-Yadun and . Already Haberlandt (1914) reviewed several functions for leaf anthocyanins proposed earlier, and listed them as light screen against the excessive light that causes damage to the photosynthetic system, and as a means of leaf heating in cold regions.…”
Section: Introductionmentioning
confidence: 99%
“…About 15% of the tree species of the temperate regions of the world change their leaf color from green to yellow or red in autumn, a percentage that can reach 70% in some regions like New England (Northeast USA) [14][15]. As leaf color change and leaf fall are thought to be controlled by temperature and precipitation [16][18], it is possible that climate change may also affect autumn phenology, with obvious biological and ecological implications [19].…”
Section: Introductionmentioning
confidence: 99%
“…the autumn leaf coloration of forests (e.g. Archetti 2009). For grasses, some authors have found evidence for climate niche conservatism among C 4 species using phylogenetic methods (Edwards and Still 2008;Webb et al 2002), whereas others have shown evidence for niche divergence of C 4 grasses (Tofts and Silvertown 2000;Edwards and Smith 2010).…”
mentioning
confidence: 99%